Design, Construction and Performance Evaluation of a Small Scale Biofuel Distiller - Onuoha, L. N. Onuoha; Nwafor, M. O. I.; Igbokwe, J. O.; Aviara, N. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
A biofuel distiller of 20 L feed capacity was designed fabricated and used to distill bioethanol from a biomass broth. The distiller consists of a 40 L volume boiler unit integrated to the combustion chamber as a cylindrical column; and a counter current cylindrical condenser of length, tube and shell internal diameter of 88 cm, 0.0191/0.15 m, inclined at 450. The reactor is a Top Lit Updraft (T-LUD) type fired with charcoal of moderate lump. Its performance evaluation was conducted using 20 L palm bunch broth as the distiller feed. The palm bunch collected from Siat Nigeria Ltd, Ubima, Rivers State, Nigeria, was physically pretreated by grinding to powder, hydrolyzed with 1.2 % dilute H2SO4, at 160°C for 30 min and fermented for 72 h with S.cerevisiae separated from palm wine. The broth was then separated from the slurry by filtering before distillation. The result of the machine evaluation showed that 817 ml bioethanol was obtained per batch at 20 min from the bubble point which took 95 min. Actual combustion efficiency was found to be 55 % with reactor power rating of 12.2 kW. The machine vaporized bioethanol fuel from the boiler feed fed at 27°C, and released the distillate at 28.3°C. Distillation efficiency was found to be greater than 90 % while the maximum productivity occurred at 10 min from the bubble point. The machine is economical, reliable, convenient to use and can stand diverse environmental conditions. It can be integrated as a waste management step in the downstream end of palm mill operations.